Palatability and oral cavity tolerability of THC:CBD oromucosal spray and possible improvement measures in multiple sclerosis patients with resistant spasticity: a pilot study. (April 2018) - Lus, Giacomo; Cantello, Roberto; Danni, Maura Chiara; Rini, Agusto; Sarchielli, Paola; Tassinari, Tiziana; Signoriello, Elisabetta
Aim: Complaints about Δ 9 -tetrahydrocannabinol (THC):cannabidiol (CBD) oromucosal spray (Sativex ® ; GW Pharma Ltd, Salisbury, UK) in the management of multiple sclerosis spasticity include unpleasant taste and oral mucosal anomalies. This pilot study assessed the use of sugar-free chewing gum and/or a refrigerated bottle of THC:CBD oromucosal spray to mitigate these effects.Materials & methods: Patients with multiple sclerosis spasticity (n = 52) at six sites in Italy who were receiving THC:CBD oromucosal spray and had associated oral mucosal effects were randomized into Group A (chewing gum; n = 15); Group B (cold bottle; n = 20); and Group C (cold bottle + chewing gum; n = 17).Results: Taste perception in patients receiving chewing gum ± cold bottle intervention (Groups A and C combined) was significantly (p = 0.0001) improved from baseline to week 4 while maintaining spasticity control.Conclusion: Patient comfort, satisfaction and treatment adherence may benefit from these interventions.